ENGLISH AS AN INTERNATIONAL LANGUAGE AND IMPLICATION ON ENGLISH TEACHER’S ROLES AND STUDENT ENGLISH LEARNING - Akbar Akbar (Institut Agama Islam Negeri Palopo, 2018)
English has been used in enormous important purposes to communicate in international level such as for academic and commerce. English as an International Language (EIL) is the use of English that enables native speakers and non-native speakers to communicate. However, there has been debate on how to teach EIL in language classroom specifically to the exposure of either the native language culture or the non-native one. This article will first define the notion of EIL before exploring the issues. Finally, this article will discuss implication on the roles of teachers regarding existing principles of EIL and student English learning